Self-care adherence and affective disorders in Barbadian adults with type 2 diabetes - Allison DaSantos; Carlisle Goddard; Dalip Ragoobirsingh (AIMS Press, 2022)
Purpose: Diabetes management requires adherence to complicated self-care behaviors. Therefore, the emotional state of the individual living with diabetes, is likely to affect their ability to comply with recommendations. This study explored the relationship of self-care adherence to diabetes distress and depression in Barbadian adults with type 2 diabetes. Methods: Adults aged 20 to 80 years, with type 2 diabetes, completed self-report questionnaires comprised of a profile section consisting of demographic and clinical characteristics; and standardized questionnaires comprising, The Diabetes Distress Scale (DDS), The Patient Health Questionnaire (PQH-9), and the Summary of Diabetes Self-care Activities Scale (SDSCA). Additionally biological measures (BP and HbA1c) were collected. Results: For the 509 participants there were no differences in adherence for males (30.8%) and females (69.2%), high diabetes distress and depression were associated with low adherence. General diet was negatively associated with BP and HbA1c; while HbA1c was positively correlated with blood glucose testing. Conclusion: Self-care non-adherence is more than a behavioral problem; it is a multidimensional phenomenon inclusive of demographic factors, condition or disease factors, psychological and social factors.